The Effectiveness of Communication Styles in the Application of E-Learning During the Covid-19 Pandemic - Dedi Rianto Rahadi; Mira Yuniar (CHANNEL: Jurnal Komunikasi, 2021)
The period of the Covid-19 pandemic requires the education sector to adapt to the learning process carried out online. The adaptation that must be done is the delivery of material that is carried out interactively using communication media. Changes in this learning process, indirectly, become a new challenge for teachers and students, in this case, lecturers and students. The purpose of this study was to determine the effectiveness of communication styles in using e-learning during the Covid-19 pandemic. The research method used is descriptive quantitative and data collection through survey methods conducted online via google form with research questions using a Likert scale. Communication can be said to be effective if the recipient of the message can receive good information from the sender of the message. The results showed that the lecturer had used a communication style following the wishes and obtained positive interactions from students. Because, when the online learning process, there is a two-way communication interaction between the message recipient (student) and the message sender (lecturer), so that students can understand the material described. The assertive communication style approach can be used to solve problems in the online learning process.